Analisis Homologi Fragmen DNA CVPDr dari Jeruk Kinkit Trophasia trifolia Menggunakan BLAST Protein Dan BLAST Nukleotida - WHISNU IDA BAGUS; I GEDE PUTU WIRAWAN; I WAYAN ADIARTAYASA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Homology Analysis Of CVPDr DNA Fragment from 13 Citrus Variety in Bali Using Nucleotide Blast And Protein Blast CVPDr from Trhiphasia trifolia is predicted to have to increase resistance fromCVPD, but the mechanism of this DNA is still largely unknown. The first step of DNAanalyzing is by using homology with Nucleotide and Protein BLAST. BLAST canidentify, similarity search, and predict the function of DNA. The goal of this researchis to compare CVPDr DNA fragment from T. Trifolia with sequences from NCBIGenbank and finding it’s significant homology using nucleotide BLAST and proteinBLAST. Nucleotide BLAST result shows that “DNA Citrus nobilis cultivar Tabanancitrus vein phloem degeneration r protein (CVPDr) gene, partial cds” have the highesthomologs, the other sequences that’s shown by BLAST does not have high enoughsimilarity to be homologus. Protein BLAST show “citrus vein phloem degeneration rprotein [Citrus nobilis]” have the highest homologs, but even if the other BLAST resulthave percentage of similarity lower than 55% there are still possibility of structuralhomolog because the E value is lower than 0.01.